Sıvı Kristaller ve Nanoyapılardan Oluşan Nanomalzemeler Üzerine Çözücü Etkisi: uv-vis Absorbans ve Floresans Spektrumları - Kara, Yunus Emre; Sıdır, Yadigar Gülseven; Horoz, Sabit (Fırat Üniversitesi, 2023)
4-Etoksibenzoik asit (4EOBA), 4-Pentilbenzoik asit (4PentBA) ve 4-Pentilfenil 4-Metilbenzoat (4PP4MetB) sıvı kristaller ve CdS, CdSe ile ZnS nanopartikülleri arasındaki etkileşimleri farklı çözücüler içerisinde incelenmiştir. Bunun için çözücü ve nanopartikül içeren LC bileşiklerden oluşan yeni malzemelerin absorbans ve floresans spektrumları kullanılarak incelenmiştir. Absorbans ve floresans elektronik geçişleri yorumlanır. Sıvı kristallerin floresansı, nanomalzemelerin floresansının dalga boyları arasındaki kaymalarda incelenmiştir. 4EOBA-CdS-DMSO ve 4EOBA-CdSe-DMSO'nun maksimum floresans dalga boylarında 4EOBA-DMSO'ya göre maviye kayma meydana geldiği söylenebilir. Öte yandan, 4EOBA-ZnS-DMSO çözeltisinde, floresan bandında kırmızıya kayma meydana gelirken, floresan bandında görülen tepe noktaları, sıvı kristaller ve nanopartiküllerin etkileşim meydana geldiğini söyleyebiliriz.

We have been investigated in different solvent medium to interactions between 4-Ethoxybenzoic acid (4EOBA), 4-Pentylbenzoic acid (4PentBA), and 4-Pentylphenyl 4-Methylbenzoate (4PP4MetB) liquid crystals with CdS, CdSe and ZnS nanoparticles. For this, the new materials composed from LC compound including the solvent and nanoparticle were investigated by use absorbance and fluorescence spectra. Electronic transitions and differences in absorbance and fluorescence spectra were interpreted. The fluorescence of liquid crystals has been defined in the shifts between wavelengths of the fluorescence of nanomaterials. It can be said that it has occurred blue shift at the maximum fluorescence wavelengths of the 4EOBA-CdS-DMSO and 4EOBA-CdSe-DMSO compared to 4EOBA-DMSO. On the other hand, we can say that in the 4EOBA-ZnS-DMSO solution occurs red shift in the fluorescence band, while the peaks seen in the fluorescence band occur in result of interaction of liquid crystals and nanoparticles.
The Solvent Effect on Nanomaterials Composed of Liquid Crystals and Nanoparticles: uv-vis Absorbance and Fluorescence Spectra
Keywords: Optical Properties of Materials; Malzemelerin Optik Özellikleri